Historical legacies - Croissant, Aurel (The handbook of political, social, and economic transformation, 2019)
How historical legacies influence democratization, help explain continuities between different types of regimes, and delineate diverging developmental processes has garnered much attention in the recent literature on historical sociology, comparative politics, and transformation research. The renewed interest in historical legacies stands in contrast with the conceptual and theoretical vagueness of the term, however, hindering both theory building and empirical analysis. Outlining the similarities and differences within legacy arguments, this chapter begins by categorizing the different types of legacies as well as distinguishing between legacies of authoritarian rule and pre-authoritarian legacies. Next, historical legacies as part of causal explanations are examined, discussing the differing views on legacies conditions, qualities, and characteristics. Lastly, historical legacies are situated in the literature on path dependence and critical junctures, revealing fundamental theoretical differences between the concepts.